Social Forestry for Community Wellfare and the Forest Sustainability - Marningot Tua Natalis Situmorang; Marningot Tua Natalis Situmorang (Jurnal Penelitian Kehutanan BONITA, 2023)
This article analyzes the Indonesian goverments program for the welfare of all Indonesian people, based on forest resource management, namely the social forestry program. In the concept of living as a state, the implementation of the social forestry program must bring the maximum benefit to the welfare of the community, in this case the community around the forest and also to the sustainability of the forest. The writing of this article uses a qualitative method by taking the research location in the jurisdiction of KPH Cianjur, BKPH Cianjur, KPH Puncak. The results showed that the social forestry program was very important to implement although there werestill some problems that needed to be corrected in practice in the field so that the social forestry program would bring the greatest benefit to the village community around the forest and the sustainability of the forest it self.Kata Kunci : perhutanan social, kesejahteraan masyarakat, kelestarian hutanÂ Â